Comparison of the outcomes of ‘component separation with mesh’, ‘component separation without mesh’ and ‘primary prosthetic repair’ methods in complex abdominal wall reconstruction - Arslan, Ufuk; Erdogdu, Umut Eren (The European Research Journal, 2021)
Objectives: The aim of this study is to compare the results of different surgical methods used in giant midline incision hernias. Methods: The records of 90 patients operated on for a midline abdominal incisional hernia were reviewed retrospectively. The patients were divided into three groups based on the surgical method used primary prosthetic repair (PPR), component separation with mesh (CSM) and component separation without mesh (CS). Two-year follow-up results were compared. Results: A statistically significant difference was noted between the groups in the transverse diameter measurement of the defect (p = 0.003). Subgroup analyses revealed that the median transverse diameter was higher in the CSM group than in the CS group (p = 0.003). There was also a statistically significant difference in the duration of surgery (p < 0.001), with a subgroup analysis revealing that the duration of surgery was longer in the CSM group than in the PPR and CS groups (PPR-CSM; p = 0.008, CSM-CS; p < 0.001). Recurrent incisional hernia, smoking and postoperative morbidity development were found to be statistically and significantly associated with recurrence (p = 0.005, p = 0.002, p < 0.001; respectively). Conclusions: The use of the CSM method for the repair of giant incisional hernias may reduce recurrence.